Development of the cycling life model of Ni-MH power batteries for hybrid electric vehicles based on real-world operating conditions. (February 2021) - Chen, Xiang; Chu, Aihua; Li, Dan; Yuan, Yinnan; Fan, Xueliang; Deng, Yelin
Highlights: The first cycling life study of Ni-MH battery pack through 12, 000 cycles of real-world battery operating condition test. A semi-empirical life time aging model has been developed for the Ni-MH battery pack. DOD is the most important factors affecting the cycle life of the Ni-MH battery in HEV conditions. The Ah-throughout is found to have little effect on aging process of the Ni-MH battery pack. Abstract: For the hybrid electric vehicle (HEV), accurate prediction of the remaining use life for the power batteries under actual operating conditions is of great significance to the battery power state of charge (SOC) estimation, as well as to the reliability and safety. However, there is little study available to evaluate the battery degradation behavior in real applications. Current battery degradation model is mostly established based on laboratory condition. In such case, charging/discharging scenarios are mostly constant across the battery cycle, and thus, they may be not a good representative of the working condition of the Ni-MH in real application where charging/discharging are frequently altered. Therefore, in this paper, the cycle life degradation characteristics of Ni-MH batteries for HEVs were studied, and an experienced model of cycle life is established based on the data from the real-world driving settings. The cycle life results indicated that the capacity loss is strongly impacted by the charge and discharge rate (C-rate), temperature, and depth of discharge (DOD). A large cycle test matrix is used to collect battery life data to build the model. The test matrix parameters include temperature (25 °C, 45 °C, 55 °C), DOD (0.5, 0.8, 1) and C-rate (1C, 2C, 5C). To verify the reliability of the life model applied to the HEV, the equivalent cycle life test verification of the real vehicle road spectrum was carried out. The test results show that the model can characterize the battery's decay process well.